ON Weak g *sD -Sets And Associative Separation Axioms - Mahmood, Sabiha I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we introduce new classes of sets called g *sD -sets , g *sD −α -sets , g *spreD − sets , g *sbD − -sets and g *sD −β -sets . Also, we study some of their properties and relations among them . Moreover, we use these sets to define and study some associative separation axioms .